A slurry pump
By applying alloys and ceramic coatings on the surface of the overflow components of the slurry pump, the corrosion, cavitation and wear problems caused by the acidic and high chloride ion environment of the slurry pump are solved, and the corrosion resistance and service life of the equipment are improved.
Patent Information
- Application Number
- CN201911272296.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-12-12
AI Technical Summary
During long-term operation of the slurry circulation pump, corrosion, cavitation and wear problems caused by acidic and high chloride ion environments, resulting in reduced desulfurization efficiency and short service life of the equipment.
The synergistic coupling of alloy coating and ceramic coating is applied to the surface of the overflow component of the slurry pump. The alloy coating is used as the intermediate layer, the ceramic coating is used as the surface layer, and the ceramic coating fills the micropores in the alloy coating to prevent corrosion Media infiltration.
It significantly improves the corrosion resistance, cavitation and wear performance of the slurry pump, extends the service life of the equipment, and reduces the damage to the underlying metal by corrosion.
Smart Images

Figure CN110821837B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of pump machinery, and in particular to a slurry pump. Background Art
[0002] At present, thermal power units generally adopt wet flue gas desulfurization systems, represented by the limestone-gypsum method. Limestone is prepared into a slurry of a certain concentration and stored in a desulfurization tower. The slurry is circulated to the spray layer at the top of the desulfurization tower through several slurry circulation pumps arranged outside the desulfurization tower. After the slurry is atomized, it contacts the upward countercurrent flue gas in the form of fine droplets to neutralize the SO2 in the flue gas.
[0003] The desulfurization slurry circulation pump is the core equipment in the wet flue gas desulfurization system. Whether it can operate safely and stably directly affects the desulfurization efficiency of the desulfurization system and whether the flue gas emissions meet environmental protection requirements. The pH value of the desulfurization slurry is about 5-6, which is acidic. The chloride ion content is as high as 20000-80000ppm. The slurry contains a large number of solid particles with a particle size range of several microns to hundreds of microns. Due to the acid and high chloride ion characteristics of the slurry, the circulating pump has serious corrosion in the long-term operation process. In addition, the impeller of the circulating pump rotates at high speed during operation. Under the conditions of high-speed flow and pressure change, the slurry fluid has cave-like cavitation damage on the metal surface in contact with the fluid. The desulfurization slurry used in wet desulfurization is a solid-liquid two-phase flow medium. The main solid components are gypsum crystals and a small amount of limestone, inert substances, fly ash, etc., and the mass concentration is generally 15%-20%. If the CaO content in the limestone used to prepare the slurry is too low, and the SiO2 and MgO contents are excessive, the insoluble SiO2 content in the absorber slurry will be too high, the slurry concentration will be too high for a long time, and there will be more solid particle impurities, which will aggravate the wear of the slurry circulation pump. For the above reasons, the service life of the flow components of the slurry circulation pump is short. With the aggravation of corrosion, cavitation and wear, the output of the pump drops sharply, resulting in a decrease in desulfurization efficiency, which seriously affects the safety and environmental protection indicators of the power plant operation. Therefore, it is necessary to optimize and transform the slurry circulation pump to improve the corrosion resistance, cavitation and wear resistance of the flow components.
[0004] CN202833188A discloses a super wear-resistant and anti-corrosion composite pump with low cost, high wear resistance, strong corrosion resistance, impact resistance and high temperature resistance, but its manufacturing process is relatively complicated, and it is also provided with a welded toughening net, which is not conducive to equipment maintenance. CN208138186A discloses a silicon carbide desulfurization centrifugal pump, which has good corrosion and wear resistance, and does not need to re-make the model, greatly reducing costs, better corrosion resistance and wear resistance, and long service life; however, due to the overall production of silicon carbide, it has poor toughness, poor impact resistance and cavitation performance. Summary of the invention
[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a slurry pump, which significantly improves the corrosion resistance, cavitation resistance, spalling resistance, impact resistance and wear resistance of the flow-through components through the synergistic coupling effect of the alloy coating and the ceramic coating on the surface of the flow-through components in the slurry pump, thereby extending the service life of the slurry pump.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] The present invention provides a slurry pump, wherein the flow-through surfaces of the impeller, volute, front guard plate and rear guard plate of the slurry pump are provided with coatings; the coatings include alloy coatings and ceramic coatings; the alloy coatings are intermediate coatings; and the ceramic coatings are surface coatings.
[0008] In the present invention, by arranging multiple layers of coating materials, including alloy coatings and ceramic coatings, on the flow-through surface of the slurry pump, the long-term use of the slurry pump is achieved, and the corrosion resistance, cavitation and wear resistance of the flow-through components are also improved. At the same time, the ceramic coating used as the top coating acts as a sealant for the alloy coating, filling the micropores in the alloy coating, thereby preventing corrosive media from penetrating into the coating and significantly reducing the damage caused by the corrosive media to the underlying metal and even the flow-through surface.
[0009] As a preferred technical solution of the present invention, the alloy coating comprises 74.5-84.95% tungsten carbide, 15-25% cobalt, and 0.05-0.5% rare earth oxide in terms of mass percentage.
[0010] In the present invention, the mass percentage of tungsten carbide in the alloy coating is 74.5-84.95%, for example, it can be 74.5%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84% or 84.95%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0011] In the present invention, the mass percentage of cobalt in the alloy coating is 15-25%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0012] In the present invention, the mass percentage of rare earth oxide in the alloy coating is 0.05-0.5%, for example, it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0013] The rare earth oxide in the present invention can be cerium oxide, lanthanum oxide or yttrium oxide, but is not limited to the rare earth oxides listed above. Other rare earth oxides that can achieve the same effect and function are also acceptable.
[0014] As a preferred technical solution of the present invention, the particle size of the tungsten carbide is 20-44μm, for example, it can be 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm, 40μm, 41μm, 42μm, 43μm or 44μm, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0015] Preferably, the particle size of the cobalt is 15-20 μm, for example, it can be 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, 19 μm, 19.5 μm or 20 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0016] Preferably, the particle size of the rare earth oxide is 10-15 μm, for example, it can be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0017] As a preferred technical solution of the present invention, the thickness of the alloy coating is 0.2-0.3 mm, for example, it can be 0.2 mm, 0.21 mm, 0.22 mm, 0.23 mm, 0.24 mm, 0.25 mm, 0.26 mm, 0.27 mm, 0.28 mm, 0.29 mm or 0.3 mm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0018] Preferably, the thickness of the ceramic coating is 0.3-1 mm, for example, it can be 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm, 0.85 mm, 0.9 mm, 0.95 mm or 1 mm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0019] The alloy coating in the present invention is deposited by surface engineering techniques such as plasma surfacing, spraying or laser melting.
[0020] As a preferred technical solution of the present invention, the ceramic coating includes a modified binder and ceramic particles.
[0021] As a preferred technical solution of the present invention, the content of the modified binder in the ceramic coating is 10-30%, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0022] As a preferred technical solution of the present invention, the content of ceramic particles in the ceramic coating is 70-90%, for example, it can be 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88% or 90%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0023] As a preferred technical solution of the present invention, the modified binder includes nano-SiO2 modified epoxy resin.
[0024] As a preferred technical solution of the present invention, the ceramic particles include SiC and / or Cr2O3.
[0025] As a preferred technical solution of the present invention, the particle size of the ceramic particles is 0.5-500μm, for example, it can be 0.5μm, 1μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm or 500μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0026] Preferably, the mass percentage of the ceramic particles with a particle size range of 0.5-5 μm is 0-5%, for example, it can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0027] Preferably, the mass percentage of the ceramic particles with a particle size range of 5-30 μm is 0-5%, for example, it can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0028] Preferably, the mass percentage of the ceramic particles with a particle size range of 30-500 μm is 90-100%, for example, it can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0029] In the present invention, the deposition method of the nano ceramic coating is spraying or brushing, which can be carried out in multiple times (at least 3 times) or once, and its thickness can be ensured to meet 0.3-1mm. After the coating deposition of the impeller is completed, a lathe is required for secondary processing to ensure the dimensional accuracy and roundness of the impeller, and a dynamic balancing test is performed to ensure the weight uniformity of the impeller.
[0030] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0031] (1) The slurry pump provided by the present invention ensures the coating's anti-stripping, anti-impact, anti-wear, anti-corrosion, and anti-cavitation properties through the synergistic coupling of the alloy coating and the ceramic coating.
[0032] (2) The flow-through surface of the slurry pump provided by the present invention has high corrosion resistance, cavitation and wear resistance, and its service life is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a metallographic picture of the coating on the flow surface of the slurry pump provided in Example 1 of the present invention.
[0034] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0036] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:
[0037] Example 1
[0038] This embodiment provides a slurry pump, wherein the flow-through surfaces of the impeller, the volute, the front guard plate and the rear guard plate of the slurry pump are provided with a coating; the coating includes an alloy coating as an intermediate coating and a ceramic coating as a surface coating;
[0039] The alloy coating comprises 81.5% tungsten carbide, 18% cobalt and 0.5% rare earth oxide in terms of mass percentage; the particle size of the tungsten carbide is 25 μm; the particle size of the cobalt is 20 μm; the particle size of the rare earth oxide is 10 μm; the thickness of the alloy coating is 0.3 mm; and the thickness of the ceramic coating is 0.5 mm.
[0040] The ceramic coating includes a modified binder and ceramic particles; the content of the modified binder in the ceramic coating is 18%; the content of ceramic particles in the ceramic coating is 82%; the modified binder includes nano-SiO2 modified epoxy resin; the ceramic particles include SiC; the particle size of the ceramic particles is 0.5-500μm; the mass percentage of the ceramic particles with a particle size range of 0.5-5μm is 3%; the mass percentage of the ceramic particles with a particle size range of 5-30μm is 5%; the mass percentage of the ceramic particles with a particle size range of 30-500μm is 82%.
[0041] The above slurry pump was subjected to hardness test (GB / T 4340.1-2009), wear resistance test (GB / T 23988-2009, falling sand method), salt spray test (GB / T 10125-1997), cavitation resistance test (GB / T 6383-2009), and coating bonding strength (GB / T 8642-2002). The metallographic picture of the coating on the flow surface of the slurry pump is shown in FIG. Figure 1 The specific test results are shown in Table 1.
[0042] Example 2
[0043] This embodiment provides a slurry pump, wherein the flow-through surfaces of the impeller, the volute, the front guard plate and the rear guard plate of the slurry pump are provided with a coating; the coating includes an alloy coating as an intermediate coating and a ceramic coating as a surface coating;
[0044] The alloy coating comprises 83.7% tungsten carbide, 16% cobalt and 0.3% rare earth oxide in terms of mass percentage; the particle size of the tungsten carbide is 30 μm; the particle size of the cobalt is 16 μm; the particle size of the rare earth oxide is 12 μm; the thickness of the alloy coating is 0.3 mm; and the thickness of the ceramic coating is 1 mm.
[0045] The ceramic coating comprises a modified binder and ceramic particles; the content of the modified binder in the ceramic coating is 15%; the content of the ceramic particles in the ceramic coating is 85%; the modified binder comprises nano-SiO2 modified epoxy resin; the ceramic particles comprise SiC; the particle size of the ceramic particles is 0.5-500 μm; the mass percentage of the ceramic particles with a particle size range of 0.5-5 μm is 2%; the mass percentage of the ceramic particles with a particle size range of 5-30 μm is 8%; the mass percentage of the ceramic particles with a particle size range of 30-500 μm is 90%.
[0046] The above slurry pump was subjected to hardness test (GB / T 4340.1-2009), wear resistance test (GB / T 23988-2009, falling sand method), salt spray test (GB / T 10125-1997), cavitation resistance test (GB / T 6383-2009), and coating bonding strength (GB / T 8642-2002). The specific test results are shown in Table 1.
[0047] Example 3
[0048] This embodiment provides a slurry pump, wherein the flow-through surfaces of the impeller, the volute, the front guard plate and the rear guard plate of the slurry pump are provided with a coating; the coating includes an alloy coating as an intermediate coating and a ceramic coating as a surface coating;
[0049] The alloy coating comprises 75.5% tungsten carbide, 24% cobalt and 0.5% rare earth oxide in terms of mass percentage; the particle size of the tungsten carbide is 20 μm; the particle size of the cobalt is 15 μm; the particle size of the rare earth oxide is 10 μm; the thickness of the alloy coating is 0.25 mm; and the thickness of the ceramic coating is 0.3 mm.
[0050] The ceramic coating includes a modified binder and ceramic particles; the content of the modified binder in the ceramic coating is 20%; the content of the ceramic particles in the ceramic coating is 80%; the modified binder includes nano-SiO2 modified epoxy resin; the ceramic particles include SiC; the particle size of the ceramic particles is 0.5-500μm; the mass percentage of the ceramic particles with a particle size range of 0.5-5μm is 4%; the mass percentage of the ceramic particles with a particle size range of 5-30μm is 4%; the mass percentage of the ceramic particles with a particle size range of 30-500μm is 92%.
[0051] The above slurry pump was subjected to hardness test (GB / T 4340.1-2009), wear resistance test (GB / T 23988-2009, falling sand method), salt spray test (GB / T 10125-1997), cavitation resistance test (GB / T 6383-2009), and coating bonding strength (GB / T 8642-2002). The specific test results are shown in Table 1.
[0052] Example 4
[0053] This embodiment provides a slurry pump, wherein the flow-through surfaces of the impeller, the volute, the front guard plate and the rear guard plate of the slurry pump are provided with a coating; the coating includes an alloy coating as an intermediate coating and a ceramic coating as a surface coating;
[0054] The alloy coating comprises 78.5% tungsten carbide, 21% cobalt and 0.5% rare earth oxide in terms of mass percentage; the particle size of the tungsten carbide is 40 μm; the particle size of the cobalt is 20 μm; the particle size of the rare earth oxide is 15 μm; the thickness of the alloy coating is 0.2 mm; and the thickness of the ceramic coating is 0.8 mm.
[0055] The ceramic coating comprises a modified binder and ceramic particles; the content of the modified binder in the ceramic coating is 25%; the content of the ceramic particles in the ceramic coating is 75%; the modified binder comprises nano-SiO2 modified epoxy resin; the ceramic particles comprise SiC; the particle size of the ceramic particles is 0.5-500 μm; the mass percentage of the ceramic particles with a particle size range of 0.5-5 μm is 2%; the mass percentage of the ceramic particles with a particle size range of 5-30 μm is 5%; the mass percentage of the ceramic particles with a particle size range of 30-500 μm is 93%.
[0056] The above slurry pump was subjected to hardness test (GB / T 4340.1-2009), wear resistance test (GB / T 23988-2009, falling sand method), salt spray test (GB / T 10125-1997), cavitation resistance test (GB / T 6383-2009), and coating bonding strength (GB / T 8642-2002). The specific test results are shown in Table 1.
[0057] Comparative Example 1
[0058] The only difference from Example 2 is that the slurry pump in this comparative example is only provided with an alloy coating; the above-mentioned slurry pump is subjected to a hardness test (GB / T 4340.1-2009), a wear resistance test (GB / T 23988-2009, falling sand method), a salt spray test (GB / T10125-1997), a cavitation resistance test (GB / T 6383-2009), and a coating bonding strength (GB / T 8642-2002). The specific test results are detailed in Table 1.
[0059] Comparative Example 2
[0060] The only difference from Example 2 is that the slurry pump in this comparative example is only provided with a ceramic coating; the above-mentioned slurry pump is subjected to a hardness test (GB / T 4340.1-2009), a wear resistance test (GB / T 23988-2009, falling sand method), a salt spray test (GB / T10125-1997), a cavitation resistance test (GB / T 6383-2009), and a coating bonding strength (GB / T 8642-2002). The specific test results are shown in Table 1.
[0061] Table 1 Test results of performance in various embodiments and comparative examples
[0062]
[0063] Based on the results of the above embodiments and comparative examples, it can be found that the slurry pump provided by the present invention achieves long-term use of the slurry pump by arranging the synergistic coupling effect of the alloy coating and the ceramic coating on the surface of the flow-through components in the slurry pump, and also improves the corrosion resistance, cavitation and wear performance of the flow-through components. At the same time, the ceramic coating used as the top coating acts as a sealer for the alloy coating, filling the micropores in the alloy coating, thereby preventing corrosive media from penetrating into the coating, and significantly reducing the damage caused by the corrosive media to the underlying metal and even the flow-through surface.
[0064] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0065] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0066] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0067] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A slurry pump, characterized in that: The flow-through surfaces of the impeller, volute, front guard plate and rear guard plate in the slurry pump are provided with coatings; the coatings include alloy coatings and ceramic coatings; the alloy coatings are intermediate coatings; and the ceramic coatings are surface coatings; The alloy coating comprises 74.5-84.95% tungsten carbide, 15-25% cobalt, and 0.05-0.5% rare earth oxide by mass percentage; the particle size of the tungsten carbide is 20-44 μm; the particle size of the cobalt is 15-20 μm; and the particle size of the rare earth oxide is 10-15 μm; The ceramic coating comprises a modified binder and ceramic particles; the content of the modified binder in the ceramic coating is 10-30%; the content of the ceramic particles in the ceramic coating is 70-90%; The slurry pump is used for conveying acidic and chlorine-containing desulfurization slurry.
2. The slurry pump according to claim 1, characterized in that: The thickness of the alloy coating is 0.2-0.3 mm.
3. The slurry pump according to claim 1, characterized in that: The thickness of the ceramic coating is 0.3-1 mm.
4. The slurry pump according to claim 1, characterized in that: The modified binder comprises nano-SiO2 modified epoxy resin.
5. The slurry pump according to claim 1, characterized in that: The ceramic particles include SiC and / or Cr2O3.
6. The slurry pump according to claim 1, characterized in that: The particle size of the ceramic particles is 0.5-500 μm.
7. The slurry pump according to claim 1, characterized in that: The mass percentage of the ceramic particles with a particle size range of 0.5-5 μm is 0-5%.
8. The slurry pump according to claim 1, characterized in that: The mass percentage of the ceramic particles with a particle size range of 5-30 μm is 0-5%.
9. The slurry pump according to claim 1, characterized in that: The mass percentage of the ceramic particles with a particle size range of 30-500 μm is 90-100%.
